Exploring the Efficacy of Student-Athlete Career Construction Groups on Career Development - Michael C. Cadaret; Mickaela Zaffino; Schazz Lee Sara Shaw; Zoe Beard; Terry Michael Hakala (Journal of Clinical Sport Psychology, 2025)
This study tested the feasibility and efficacy of a career construction intervention group based on career construction theory, best practices in career counseling, values exploration, and goal setting. This pilot study measured pre and post scores of Career Decision-Making Self-Efficacy, Career Adapt-Abilities Scale, Athletic Identity Measurement Scale and vocational hope with 81 student-athletes across three college teams. Results demonstrated significant increases on total and subscale scores of career decision-making self-efficacy and Career Adapt-Abilities Scale. The Athletic Identity Measurement Scale scores were nonsignificant apart from “negative affectivity,” which significantly lowered postintervention. Vocational hope did not significantly change as a result of the intervention. Results and detail of the study are presented, and implications for practice are discussed.